Investigating Students’ Motivation in Learning Speaking through Online Learning - Luthfi Hamida Lestari; Slamet ASARI (RADINKA JAYA UTAMA PUBLISHER, 2023)
The purpose of this research is to explore how students' learning motivation in learning speaking through online learning and how the students' speaking ability during the learning process. A quantitative design was taken to achieve research objectives with speaking tests and questionnaires as instruments. The participants of this study were 8th-grade students at the Kaengsriphoom school for the 2020/2021 academic year with a total of 25 students. After the analysis, by dividing the levels of both students’ motivation and student speaking ability into 3 categories Low, Moderate, and High, the study found that the level of student motivation in carrying out learning through online learning was in the moderate category, while student speaking ability also dominated in the moderate category. From all the research questions and findings, it can be concluded that students’ motivation and students' speaking ability in learning speaking through online learning is a moderate category.